Cervical Cancer Awareness and Screening Practices Among Women in Benghazi: A Cross-Sectional Study (2023) - Elsaid, Amina Muftah (Libyan International Medical University Journal, 2025)
Cervical cancer remains a significant public health concern in Libya, yet awareness and screening rates remain low.This study assessed knowledge, beliefs, and attitudes toward cervical cancer among women in Benghazi.A cross-sectional study was conducted among 137 women attending a cervical cancer awareness campaign in January 2023. Data were collected using a structured, self-administered questionnaire assessing demographics, knowledge (7-item scale), beliefs (4-item scale), and attitudes (11-item scale). Responses were scored and categorized as poor/good knowledge, unfavorable/favorable beliefs, and negative/positive attitudes. Statistical analysis was performed using SPSS v25, with chi-square and Fisher's exact tests to examine associations between demographic factors and outcomes.The mean age of participants was 40 ± 11.7 years, with 34.3% aged 40 to 50 years. Most were married (66.4%), had a university degree (43.8%), and 51.8% were unemployed. Note that 65.7% had poor knowledge, 83.9% held unfavorable beliefs, and 61.1% had negative attitudes toward cervical cancer. No significant association was found between age and knowledge, beliefs, or attitudes. However, married, educated, and employed women had significantly higher knowledge levels (p < 0.05). No significant differences were observed between demographics and beliefs or attitudes. Only 16% had ever undergone a Pap smear, and 62% were unaware of the human papillomavirus (HPV) vaccine.The study revealed alarmingly low knowledge, unfavorable beliefs, and negative attitudes toward cervical cancer, along with minimal screening uptake. These findings suggest inadequate public health education and a lack of structured screening programs in Libya. Targeted awareness campaigns, improved access to screening, and HPV vaccination programs are urgently needed to reduce cervical cancer burden.
Keywords: awareness; practice; cervical cancer; screening; Benghazi, Libya